Economic considerations of antifungal prophylaxis in patients undergoing surgical procedures - Cataldo, Maria Adriana (Dove Medical Press, 2011)
Fungi are a frequent cause of nosocomial infections, with an incidence that has increased significantly in recent years, especially among critically ill patients who require intensive care unit (ICU) admission. Among ICU patients, postsurgical patients have a higher risk of Candida infections in the bloodstream. In consideration of the high incidence of fungal infections in these patients, their strong impact on mortality rate, and of the difficulties in Candida diagnosis, some experts suggest the use of antifungal prophylaxis in critically ill surgical patients. A clinical benefit from this strategy has been demonstrated, but the economic impact of the use of antifungal prophylaxis in surgical patients has not been systematically evaluated, and its cost–benefit ratio has not been defined. Whereas the costs associated with treating fungal infections are very high, the cost of antifungal drugs varies from affordable (ie, the older azoles) to expensive (ie, echinocandins, polyenes, and the newer azoles). Adverse drug-related effects and the possibly increased incidence of fluconazole resistance and of isolates other than Candida albicans must also be taken into account. From the published studies of antifungal prophylaxis in surgical patients, a likely economic benefit of this strategy could be inferred, but its usefulness and cost–benefits should be evaluated in light of local data, because the available evidence does not permit general recommendations.